2023
DOI: 10.1021/acsami.3c05892
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Electronic Interaction in In2O3/Poly(3,4-ethylenedioxythiophene)-Modified Carbon Heterostructures for Enhanced Electroreduction of CO2 to Formate

Abstract: Formate, as an important chemical raw material, is considered to be one of the most promising products for industrialization among CO2 electroreduction reaction (CO2RR) products, but it still suffers from poor selectivity and a low formation rate at a high current density on account of the competitory hydrogen evolution reaction. Herein, the heterogeneous nanostructure was constructed by anchoring In2O3 nanoparticles on poly­(3,4-ethylenedioxythiophene) (PEDOT)-modified carbon black (In2O3/PC), in which the PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In 2 O 3 /PC presents an outstanding electrocatalytic selectivity for formate with an FE of 95.4%, an extremely high formate current density of 239.8 mA cm −2 at −1.18 V vs. RHE, and a high stability for 75 h continuous electrolysis test. 121 There are strong interface electronic interactions between In metal and PC in the In/PC heterojunction confirmed by both experiments and DFT results, elevating the p-band center of In metal active sites to the Fermi level, resulting in the lower formation energies of the *OCHO, which is the key intermediate for converting CO 2 to the target production formate.…”
Section: Heterojunction Catalysts For Electrocatalytic Co2–hcoox Inte...mentioning
confidence: 65%
See 2 more Smart Citations
“…In 2 O 3 /PC presents an outstanding electrocatalytic selectivity for formate with an FE of 95.4%, an extremely high formate current density of 239.8 mA cm −2 at −1.18 V vs. RHE, and a high stability for 75 h continuous electrolysis test. 121 There are strong interface electronic interactions between In metal and PC in the In/PC heterojunction confirmed by both experiments and DFT results, elevating the p-band center of In metal active sites to the Fermi level, resulting in the lower formation energies of the *OCHO, which is the key intermediate for converting CO 2 to the target production formate.…”
Section: Heterojunction Catalysts For Electrocatalytic Co2–hcoox Inte...mentioning
confidence: 65%
“…Among all the catalysts investigated to date, In-based electrocatalysts with excellent selectivity toward targeted formate and non-toxicity have attracted much attention. 121 Sn and Bi metals, as the low-cost, low-toxic, and earth-abundant metal elements, show high selectivity to formic acid and a high activity during the electrocatalytic CO 2 reduction reaction. 120,122 Therefore, Sn-, Bi-, and In-based catalysts are promising candidates for large-scale real-world use, because of their merits of low price, abundance, and environmental benignancy, compared to the noble metals Au, Pd, and Ag, as well as the toxic metals Pb, Hg, and Cd.…”
Section: Heterojunction Catalysts For Electrocatalytic Co2–hcoox Inte...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the adsorption-free energy of intermediates and the selectivity of specific products can also be promoted by forming heterostructure for CO 2 RR. In recent years, there have been many achievements in this area, such as the design of InO x @CuO, [222] CuO-In 2 O 3 , [223] Cu/In, [206] In 2 O 3 -ZnO, [224] In-O-ultrathin-SnS 2 , [225] In 2 O 3 /PC, [226] In/In 2 O 3−x , [227] In 2 O 3 -CeO x [228] with heterostructures. Those materials have been demonstrated that the constructed heterostructures can greatly enhance the performance of In-based catalysts for CO 2 RR.…”
Section: Interface Structure Designmentioning
confidence: 99%
“…Heterostructures are extremely helpful to enhance the selectivity of the most common formic acid products in In-based catalysts, such as the constructed In 2 O 3 /PC, [226] In/In 2 O 3−x [227] and other heterojunction materials. The recently proposed a special crystalline-amorphous heterostructure, which shows unique potential in CO 2 RR.…”
Section: Interface Structure Designmentioning
confidence: 99%